Negative electrode material and preparation method and application thereof

By fully covering nano-silicon with graphene, a super-large continuous conductive network is constructed, which solves the battery capacity attenuation problem caused by the volume change of the silicon anode material during charging and discharging, effectively alleviates volume expansion and powdering, and improves the cycle stability of the battery. properties and conductivity.

CN119340363APending Publication Date: 2025-01-21SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411450289.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The violent volume changes of existing silicon negative electrode materials during charging and discharging lead to increased stress, destroying the solid electrolyte interface, causing rapid attenuation of battery capacity, and methods such as nanoification and surface coating have problems such as high cost and general conductivity.

Method used

Graphene is used to fully cover nano-silicon to build an ultra-large continuous conductive network. The negative electrode material is prepared through spray granulation to achieve uniform combination of graphene and nano-silicon.

Benefits of technology

Effectively alleviate the volume expansion and powder of silicon materials, improve the cycle stability and high capacity maintenance rate of the battery, significantly increased conductivity and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340363A_ABST
    Figure CN119340363A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode material and a preparation method and application thereof. The negative electrode material comprises nano silicon and graphene, and the graphene coats the nano silicon; wherein the single-layer rate of the graphene is 90%-99%, the lamellar size is 0.5-100 [mu] m, and the mass ratio of the nano silicon to the graphene is (0.2-10): 1. The negative electrode material can be prepared by spray granulation of a mixed solution containing nano silicon, graphene oxide and a solvent. The negative electrode material has good stability and high conductivity, and when the negative electrode material is actually applied to a battery, the problems of volume expansion and pulverization of a silicon material can be effectively relieved, and meanwhile, the high capacity retention rate is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a negative electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are currently the most promising chemical energy storage batteries due to their high discharge voltage, high energy density, high power density, long cycle life and environmental friendliness. They are also ideal supporting power sources for portable electronic products, mobile products, electric vehicles and energy storage equipment. Due to the rapid development of portable electronic devices, mobile products and electric vehicles, the power density requirements of batteries are constantly increasing, and the demand for new lithium-ion batteries with high energy density and high specific capacity is also becoming increasingly urgent. The negative electrode material controls the storage and release of lithium ions in lithium batteries, which is the key to the development of new lithium-ion batteries. The theoretical capacity of traditional graphite negative electrodes is only 372mAh / g, which has seriously restricted the development of the entire lithium-ion battery industry. Therefore, it is urgent to develop new negative electrode materials with high specific capacity.

[0003] Silicon (Si) negative electrode materials have the advantages of high theoretical capacity, low discharge platform, abundant resources and good safety performance. Its theoretical capacity can reach 3579mAh / g, which is an electrode material that is very likely to replace commercial graphite negative electrodes. However, the drastic volume change (greater than 300%) of Si negative electrode materials during charging and discharging hinders the use of pure Si. The stress generated by the drastic volume change will destroy the solid electrolyte interface (SEI) film, causing the continuous formation of the SEI film, and then continuously consuming the limited electrolyte in the battery, causing the battery capacity to decay rapidly. At the same time, the drastic volume change will also cause the powdering of the pole piece and the shedding of the active material, leading to battery failure. In response to the above problems, researchers have explored a variety of methods to improve the cycle performance of silicon negative electrode materials, generally including the following aspects: (1) Silicon nano-sizing, by preparing nano-scale silicon materials (silicon nanospheres, silicon nanowires, silicon nanofilms), etc., to reduce the absolute volume change of silicon materials during the charge and discharge process, thereby slowing down the pulverization and shedding of electrode materials; (2) Surface coating of silicon materials, generally by coating a layer of carbon material on the surface of silicon materials, thereby restraining the volume expansion of silicon during the charge and discharge process, thereby improving its cycle performance; (3) Porous carbon deposition of nanosilicon. This method has been a research hotspot in recent years. Silicon-carbon composite materials are prepared by taking advantage of the opportunity of silane cracking inside porous carbon materials to produce nanosilicon. The stability of the carbon skeleton can alleviate the volume expansion of nanosilicon, thereby improving the cycle stability of the material.

[0004] In the above methods, nano-sizing of silicon cannot completely alleviate the problem of pulverization of the electrode. Usually, the capacity of the battery will decay rapidly after dozens of cycles, and the cost of preparing extremely small-sized (less than 10nm) nano-silicon is very high; the coating scheme of silicon material has limited strength of the coating layer, and the elasticity of the coating layer after carbonization is usually low. During the charging and discharging process, the outer shell is easily squeezed by the inner silicon material, causing rapid decay of capacity; although porous carbon-deposited nano-silicon can better alleviate the volume expansion of silicon, this method has high material and energy consumption costs, and the carbon skeleton has not been graphitized, and the conductivity is general.

[0005] To this end, there is an urgent need for a negative electrode material that can effectively alleviate the volume expansion of silicon materials, maintain high conductivity, and effectively maintain high battery capacity. Summary of the invention

[0006] In order to overcome the above defects existing in the existing silicon-containing negative electrode materials, the present invention provides a negative electrode material and its preparation method and application. The negative electrode material has good stability and high conductivity. When actually used in batteries, it can effectively alleviate the volume expansion and pulverization problems of silicon materials while ensuring high capacity retention.

[0007] To achieve the above purpose, the technical solution provided by the present invention is as follows:

[0008] The present invention provides a negative electrode material, which comprises nano-silicon and graphene, wherein the graphene covers the nano-silicon; wherein:

[0009] In the coating area formed by the coating, the same coating area contains a plurality of nano-silicon;

[0010] The monolayer rate of the graphene is 90%-99%;

[0011] The graphene sheet size is 0.5 μm-100 μm;

[0012] The mass ratio of the nano-silicon to graphene is (0.2-10):1.

[0013] In the present invention, the meaning of the sheet size is: the average size of the long side of the edge of the graphene sheet in the coating structure, and those skilled in the art will know its specific meaning.

[0014] In some embodiments, the monolayer ratio of the graphene is 95%-99%, such as 96%, 97% or 98%.

[0015] In some embodiments, the graphene sheet size is 30-100 μm, such as 32 μm or 35 μm.

[0016] In some embodiments, the mass ratio of the nano-silicon to graphene is (1-5):1, such as 3:1 or 4:1.

[0017] In some embodiments, the graphene sheet thickness is 0.7-10 nm, preferably 1-5 nm, such as 1.4 nm or 2.8 nm.

[0018] In some embodiments, the particle size D50 of the nano-silicon is 20-100 nm, for example, 50 nm.

[0019] In some embodiments, the particle size D50 of the negative electrode material is 0.5-25 μm, preferably 2-10 μm, such as 3 μm or 5 μm.

[0020] In some embodiments, the powder resistivity of the negative electrode material under a pressure of 20 MPa is lower than 20 Ω·cm, preferably lower than 15 Ω·cm, such as 12.5 Ω·cm or 1.6 Ω·cm.

[0021] The present invention also provides a method for preparing a negative electrode material, which comprises the following steps: spraying and granulating a mixed solution containing nano-silicon, graphene oxide and a solvent to obtain the negative electrode material; wherein:

[0022] The monolayer rate of the graphene oxide is 90%-99%;

[0023] The sheet size of the graphene oxide is 0.5 μm-100 μm;

[0024] The mass ratio of the nano-silicon and graphene oxide is (0.2-10):1.

[0025] In the present invention, the monolayer rate of the graphene oxide can be obtained through AFM detection results. Generally, it can be obtained by measuring the thickness of the graphene oxide by AFM in combination with the theoretical thickness of a single-layer graphene oxide. Those skilled in the art will know its specific meaning.

[0026] In some embodiments, the monolayer ratio of the graphene oxide is 95%-99%, such as 96%, 97% or 98%.

[0027] In some embodiments, the graphene oxide has a sheet size of 30-100 μm, such as 32 μm or 35 μm.

[0028] In some embodiments, the mass ratio of the nano-silicon to graphene oxide is (1-5):1, such as 3:1 or 4:1.

[0029] In some embodiments, the graphene oxide has a sheet thickness of 0.7-10 nm, preferably 1-5 nm, such as 1.4 nm or 2.8 nm.

[0030] In some embodiments, the particle size D50 of the nano-silicon is 20-100 nm, for example, 50 nm.

[0031] In some embodiments, the solvent is water and / or alcohol, such as deionized water.

[0032] In some embodiments, the preparation of the mixed solution includes: mixing the nano-silicon, graphene oxide and a solvent, and the mixing is performed, for example, under stirring conditions.

[0033] In some embodiments, the outlet temperature of the spray granulation is preferably 150-300°C, such as 210°C or 270°C.

[0034] In some embodiments, the flow rate of the spray granulation is preferably 100-3000 mL / h, such as 200 mL / h or 500 mL / h.

[0035] In some embodiments, the method for preparing the negative electrode material comprises the following steps: mixing a dispersion containing the graphene oxide and the solvent with the nano-silicon to obtain a mixed solution, and spray granulating to obtain the negative electrode material.

[0036] In some preferred embodiments, the preparation of the dispersion comprises the following steps:

[0037] The graphene oxide powder is dispersed in the solvent to obtain the dispersion; or the graphene oxide aqueous solution is diluted with the solvent to obtain the dispersion.

[0038] Wherein, the dispersion is preferably ultrasonic dispersion or stirring dispersion.

[0039] The concentration of the dispersion is preferably 0.1-5 mg / mL, such as 2.5 mg / mL.

[0040] The present invention also provides a negative electrode material, which is prepared by the negative electrode material preparation method as described above.

[0041] In the present invention, the negative electrode material prepared by the negative electrode material preparation method is as described above, that is, the negative electrode material comprises nano-silicon and graphene, and the graphene covers the nano-silicon; wherein, in the coating area formed by the coating, the same coating area comprises a plurality of nano-silicon.

[0042] In the present invention, during the spray granulation process, the graphene oxide is dehydrated to obtain graphene, and naturally curls up as the solvent evaporates, thereby achieving surface coating of the nano-silicon. The monolayer rate, sheet size and sheet thickness of the obtained graphene are consistent with those of the graphene oxide, that is, the process mainly undergoes morphological changes, and the specific structural parameters do not change. As for the mass ratio of graphene oxide and nano-silicon, the graphene oxide only removes water molecules during the whole process, and the mass loss is relatively small, so the change in the mass ratio of the final obtained graphene and nano-silicon can be ignored.

[0043] The present invention also provides an application of the negative electrode material as mentioned above in the field of electrochemistry.

[0044] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0045] The reagents and raw materials used in the present invention are commercially available.

[0046] The positive and progressive effects of the present invention are:

[0047] The negative electrode material of the present invention is a graphene-coated nano-silicon material, which constructs a large continuous conductive network and effectively increases the conduction rate of electrons inside the material. The negative electrode material has good stability and low resistance performance. When actually used in batteries, it can effectively alleviate the volume expansion and pulverization problems of silicon materials, while ensuring a capacity retention rate of more than 80%. The overall preparation process is simple, efficient, and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a SEM image of the negative electrode material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0049] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0050] Unless otherwise specified, in the following examples and comparative examples, the graphene oxide powder or graphene oxide aqueous solution used was purchased from Suzhou Carbon Graphene Technology Co., Ltd., and the specific parameters were directly provided by the manufacturer.

[0051] Example 1

[0052] The negative electrode material of this embodiment is prepared according to the following steps:

[0053] (1) 0.5 g of graphene oxide powder (monolayer rate 95%, average thickness 2.8 nm, average flake size 32 μm) was fully dispersed in 100 mL of deionized water by ultrasonic treatment to obtain a graphene oxide dispersion with a concentration of 5 mg / mL;

[0054] (2) adding 2 g of nano-silicon powder (D50 = 50 nm) to the graphene oxide dispersion, stirring and dispersing the mixture evenly to obtain a mixed dispersion;

[0055] (3) The mixed dispersion was spray dried using a spray dryer (outlet temperature of 210° C., flow rate of 200 mL / h) to obtain the negative electrode material.

[0056] Example 2

[0057] The negative electrode material of this embodiment is prepared according to the following steps:

[0058] (1) Add 300 mL of deionized water to 100 mL of graphene oxide aqueous solution (10 mg / mL, monolayer rate 98%, average lamella thickness 1.4 nm, average lamella size 35 μm) to obtain a graphene oxide dispersion with a concentration of 2.5 mg / mL;

[0059] (2) adding 3 g of nano-silicon powder (D50 = 50 nm) into the graphene oxide dispersion, stirring and dispersing the mixture evenly to obtain a mixed dispersion;

[0060] (3) The mixed dispersion was spray dried using a spray dryer (outlet temperature of 270° C., flow rate of 500 mL / h) to obtain the negative electrode material.

[0061] Comparative Example 1

[0062] The negative electrode material of this comparative example was prepared according to the following steps:

[0063] (1) Add 300 mL of deionized water to 100 mL of graphene oxide aqueous solution (10 mg / mL, monolayer rate 98%, average lamella thickness 2.4 nm, average lamella size 35 μm) to obtain a graphene oxide dispersion with a concentration of 2.5 mg / mL;

[0064] (2) adding 30 g of nano silicon powder (D50 = 50 nm) into the graphene oxide dispersion, stirring and dispersing the mixture evenly to obtain a mixed dispersion;

[0065] (3) The mixed dispersion was spray dried using a spray dryer (outlet temperature of 270° C., flow rate of 500 mL / h) to obtain the negative electrode material.

[0066] Comparative Example 2

[0067] The negative electrode material of this comparative example was prepared according to the following steps:

[0068] (1) Add 300 mL of deionized water to 100 mL of graphene oxide aqueous solution (10 mg / mL, average thickness of 15 nm, monolayer rate of 82%, average sheet size of 32 μm) to obtain a graphene oxide dispersion with a concentration of 2.5 mg / mL;

[0069] (2) adding 3 g of nano-silicon powder (D50 = 50 nm) into the graphene oxide dispersion, stirring and dispersing the mixture evenly to obtain a mixed dispersion;

[0070] (3) The mixed dispersion was spray dried using a spray dryer (outlet temperature of 270° C., flow rate of 500 mL / h) to obtain the negative electrode material.

[0071] Comparative Example 3

[0072] The negative electrode material of this comparative example was prepared according to the following steps:

[0073] (1) Add 300 mL of deionized water to 100 mL of graphene oxide aqueous solution (10 mg / mL, average thickness of 1.5 nm, monolayer rate of 99%, average sheet size of 0.3 μm) to obtain a graphene oxide dispersion with a concentration of 2.5 mg / mL;

[0074] (2) adding 3 g of nano-silicon powder (D50 = 50 nm) into the graphene oxide dispersion, stirring and dispersing the mixture evenly to obtain a mixed dispersion;

[0075] (3) The mixed dispersion was spray dried using a spray dryer (outlet temperature of 270° C., flow rate of 500 mL / h) to obtain the negative electrode material.

[0076] Effect Example

[0077] The negative electrode materials obtained in Examples 1-2 and Comparative Examples 1-3 were characterized as follows:

[0078] (1) Morphological characterization

[0079] The morphology was characterized by scanning electron microscopy (SEM).

[0080] The characterization results of Example 1 are as follows Figure 1 As shown in the figure, the size of the graphene sheet in the negative electrode material is much larger than that of nano-silicon, and multiple nano-silicon particles are evenly wrapped in the graphene sheet; and it has been measured that the particle size D50 of the negative electrode material is about 5μm.

[0081] The negative electrode material obtained in Example 2 also satisfies the above coating structure, and the particle size D50 is about 3 μm.

[0082] The particle size D50 of the negative electrode material obtained in Comparative Example 1 is about 2 μm, and some of the nano silicon powder is not coated. The particle size D50 of the negative electrode material obtained in Comparative Example 2 is about 5 μm, and a small amount of nano silicon powder is not coated. The particle size D50 of the negative electrode material obtained in Comparative Example 3 is about 1.2 μm, and some of the nano silicon powder is not coated.

[0083] (2) Conductivity test

[0084] With reference to standard GBT 30835-2014, the resistance of the negative electrode material was tested by a four-probe method at a test pressure of 20 MPa.

[0085] It has been determined that the powder resistivity of the negative electrode material of Example 1 is 12.5Ω·cm, which is significantly lower than that of the original nano silicon powder (ie, without graphene coating, the powder resistivity is 2450Ω·cm), that is, the conductivity is significantly enhanced.

[0086] The powder resistivity of the negative electrode material obtained in Example 2 is 1.6Ω·cm.

[0087] The powder resistivity of the negative electrode material obtained in Comparative Example 1 is 1035Ω·cm, the powder resistivity of the negative electrode material obtained in Comparative Example 2 is 35.5Ω·cm, and the powder resistivity of the negative electrode material obtained in Comparative Example 3 is 142.0Ω·cm.

[0088] That is, compared with Examples 1-2, the resistivity of the negative electrode materials obtained in Comparative Examples 1-3 was significantly increased, and the conductivity was significantly deteriorated.

[0089] (3) Battery performance test

[0090] ①Battery assembly:

[0091] The negative electrode materials obtained in Examples 1-2 and Comparative Examples 1-3, polyvinylidene fluoride and acetylene black were mixed evenly in a mass ratio of 8:1:1, coated on copper foil to form a composite material with uniform thickness, dried in a vacuum drying oven at 120°C, and sliced ​​to form an electrode sheet. In a closed glove box filled with argon, the electrode sheet was used as a working electrode, a microporous polypropylene membrane was used as a diaphragm, a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) (containing 1.0M LiPF6) in a volume ratio of 1:1 was used as an electrolyte, and a metal lithium sheet was used as a counter electrode to assemble a CR2032 button cell.

[0092] ②Test parameters:

[0093] The charge and discharge performance of the obtained button cells was tested in the voltage range of 0.01-2V (charge and discharge rate of 100mA / g).

[0094] It was determined that the initial discharge capacity of the button cell obtained using the negative electrode material of Example 1 was 2725 mAh / g, and after 100 cycles, it still maintained 2459 mAh / g, with a capacity retention rate of 90.2%.

[0095] After the negative electrode material obtained in Example 2 was assembled into a button cell, the initial discharge specific capacity was 2073 mAh / g, and after 200 cycles, it still maintained 1685 mAh / g, with a capacity retention rate of 81.3%.

[0096] After the negative electrode material obtained in Comparative Example 1 was assembled into a button cell, the initial discharge specific capacity was 3142 mAh / g, but after 10 cycles, the capacity remained only 406 mAh / g, and after 100 cycles, the capacity remained only 152 mAh / g, and the capacity retention rate was 4.8%.

[0097] After the negative electrode material obtained in Comparative Example 2 was assembled into a button cell, the initial discharge specific capacity was 1768 mAh / g, but after 10 cycles, the capacity remained only 423 mAh / g, and after 100 cycles, the capacity remained only 106 mAh / g, and the capacity retention rate was 6.0%.

[0098] After the negative electrode material obtained in Comparative Example 3 was assembled into a button cell, the initial discharge specific capacity was 1862 mAh / g, but after 10 cycles, the capacity remained only 205 mAh / g, and after 100 cycles, the capacity remained only 52 mAh / g, and the capacity retention rate was 2.8%.

[0099] In summary, the negative electrode material of the present invention has strong conductivity and good stability. When actually used in batteries, it can effectively alleviate the volume expansion and pulverization problems of silicon materials, and still maintain a high capacity after multiple cycles. When the graphene oxide is insufficient, the graphene oxide thickness is large (the monolayer rate is low), and the graphene oxide sheet is small, the nano silicon powder cannot be effectively coated, the conductivity is significantly reduced, and the capacity decays rapidly after the battery is assembled.

Claims

1. A negative electrode material, characterized in that: The negative electrode material includes nano-silicon and graphene, and the graphene covers the nano-silicon; wherein, In the coating area formed by the coating, the same coating area contains a plurality of nano-silicon; The monolayer rate of the graphene is 90%-99%; The graphene sheet size is 0.5 μm-100 μm; The mass ratio of the nano-silicon to graphene is (0.2-10):

1.

2. The negative electrode material according to claim 1, characterized in that The monolayer rate of the graphene is 95%-99%, for example 96%, 97% or 98%; And / or, the graphene sheet size is 30-100 μm, such as 32 μm or 35 μm; And / or, the mass ratio of the nano-silicon to the graphene is (1-5):1, for example, 3:1 or 4:

1.

3. The negative electrode material according to claim 1, characterized in that The graphene sheet thickness is 0.7-10 nm, preferably 1-5 nm, for example 1.4 nm or 2.8 nm; And / or, the particle size D50 of the nano-silicon is 20-100 nm, for example, 50 nm; and / or, the particle size D50 of the negative electrode material is 0.5-25 μm, preferably 2-10 μm, for example 3 μm or 5 μm; And / or, the powder resistivity of the negative electrode material under a pressure of 20 MPa is lower than 20 Ω·cm, preferably lower than 15 Ω·cm, such as 12.5 Ω·cm or 1.6 Ω·cm.

4. A method for preparing a negative electrode material, characterized in that: The preparation method of the negative electrode material comprises the following steps: spraying and granulating a mixed solution containing nano-silicon, graphene oxide and a solvent to obtain the negative electrode material; wherein, The monolayer rate of the graphene oxide is 90%-99%; The sheet size of the graphene oxide is 0.5 μm-100 μm; The mass ratio of the nano-silicon and graphene oxide is (0.2-10):

1.

5. The method for preparing the negative electrode material according to claim 4, characterized in that: The monolayer rate of the graphene oxide is 95%-99%, for example 96%, 97% or 98%; And / or, the flake size of the graphene oxide is 30-100 μm, for example, 32 μm or 35 μm; And / or, the mass ratio of the nano-silicon to the graphene oxide is (1-5):1, for example, 3:1 or 4:

1.

6. The method for preparing the negative electrode material according to claim 4, characterized in that: The graphene oxide sheet has a thickness of 0.7-10 nm, preferably 1-5 nm, such as 1.4 nm or 2.8 nm; And / or, the particle size D50 of the nano-silicon is 20-100 nm, for example, 50 nm; And / or, the solvent is water and / or alcohol, and the water is, for example, deionized water; And / or, the preparation of the mixed solution includes: mixing the nano-silicon, graphene oxide and a solvent, wherein the mixing is performed under stirring conditions; and / or, the outlet temperature of the spray granulation is 150-300° C., for example, 210° C. or 270° C.; And / or, the flow rate of the spray granulation is 100-3000 mL / h, such as 200 mL / h or 500 mL / h.

7. The method for preparing the negative electrode material according to claim 4, characterized in that: The preparation method of the negative electrode material comprises the following steps: mixing a dispersion containing the graphene oxide and the solvent with the nano-silicon to obtain the mixed solution, and spraying and granulating to obtain the negative electrode material; Wherein, the preparation of the dispersion preferably comprises the following steps: The graphene oxide powder is dispersed in the solvent to obtain the dispersion; or the graphene oxide aqueous solution is diluted with the solvent to obtain the dispersion.

8. The method for preparing the negative electrode material according to claim 7, characterized in that: The dispersion is ultrasonic dispersion or stirring dispersion; And / or, the concentration of the dispersion is 0.1-5 mg / mL, such as 2.5 mg / mL.

9. A negative electrode material, characterized in that: The negative electrode material is prepared by the method for preparing the negative electrode material according to any one of claims 4 to 8.

10. Use of the negative electrode material according to any one of claims 1 to 3 and 9 in the field of electrochemistry.